Work climate in emergency health services during COVID-19 pandemic—An international multicenter study - Kosydar-Bochenek, Justyna; Krupa, Sabina; Religa, Dorota; Friganovic, Adriano; Oomen, Ber; Williams, Ged; Vollman, Kathleen M.; Rogado, Maria Isabelita C.; Goldsworthy, Sandra; Lopez, Violeta; Brioni, Elena; Medrzycka-Dabrowska, Wioletta (Frontiers in Public Health, 2022)
Introduction A good working climate increases the chances of adequate care. The employees of Emergency in Hospitals are particularly exposed to work-related stress. Support from management is very important in order to avoid stressful situations and conflicts that are not conducive to good work organization. The aim of the study was to assess the work climate of Emergency Health Services during COVID-19 Pandemic using the Abridged Version of the Work Climate Scale in Emergency Health Services. Design A prospective descriptive international study was conducted. Methods The 24-item Abridged Version of the Work Climate Scale in Emergency Health Services was used for the study. The questionnaire was posted on the internet portal of scientific societies. In the study participated 217 women (74.5%) and 74 men (25.4%). The age of the respondents ranged from 23 to 60 years (SD = 8.62). Among the re-spondents, the largest group were Emergency technicians (85.57%), followed by nurses (9.62%), doctors (2.75%) and Service assistants (2.06%). The study was conducted in 14 countries. Results The study of the climate at work shows that countries have different priorities at work, but not all of them. By answering the research questions one by one, we can say that the average climate score at work was 33.41 min 27.0 and max 36.0 (SD = 1.52). Conclusion The working climate depends on many factors such as interpersonal relationships, remuneration or the will to achieve the same selector. In the absence of any of the elements, a proper working climate is not possible.